2015
DOI: 10.1111/mec.13310
|View full text |Cite
|
Sign up to set email alerts
|

A population study of killer viruses reveals different evolutionary histories of two closely related Saccharomyces sensu stricto yeasts

Abstract: Microbes have evolved ways of interference competition to gain advantage over their ecological competitors. The use of secreted killer toxins by yeast cells through acquiring double-stranded RNA viruses is one such prominent example. Although the killer behaviour has been well studied in laboratory yeast strains, our knowledge regarding how killer viruses are spread and maintained in nature and how yeast cells co-evolve with viruses remains limited. We investigated these issues using a panel of 81 yeast popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 54 publications
3
45
0
Order By: Relevance
“…In the same environments, K1 or K28 strains were not found (23). K1 strains seem to be confined mainly to laboratory collections, and K28 strains have been reported recently in Saccharomyces paradoxus (38,39).…”
Section: Discussion L-a-2 Is the Helper Virus Of M2 And Is Excluded Bmentioning
confidence: 83%
See 1 more Smart Citation
“…In the same environments, K1 or K28 strains were not found (23). K1 strains seem to be confined mainly to laboratory collections, and K28 strains have been reported recently in Saccharomyces paradoxus (38,39).…”
Section: Discussion L-a-2 Is the Helper Virus Of M2 And Is Excluded Bmentioning
confidence: 83%
“…This may reflect different evolutionary rates of these two types of totiviruses in the same host or, alternatively, distinct evolutionary histories in separate hosts before the introduction of one of the viruses into yeasts carrying the other to generate strains with both together. While killer totiviruses (and thus L-A) are found in S. cerevisiae and other yeasts from the sensu stricto cluster, such as S. paradoxus or Saccharomyces uvarum (38)(39)(40), as well as in nonrelated yeasts, L-BC seems to be less widespread. We have found it to be present only in S. cerevisiae strains and absent from several S. paradoxus and S. uvarum strains so far examined (Rodríguez-Cousiño and Esteban, unpublished).…”
Section: Discussion L-a-2 Is the Helper Virus Of M2 And Is Excluded Bmentioning
confidence: 99%
“…Similarly, yeast species can be polymorphic for toxin sensitivity, and resistance evolves readily during laboratory evolution (Pieczynska, Wloch‐Salamon, Korona, & de Visser, ). As a result, a given species can include killer, sensitive, and resistant (also sometimes called “neutral”) phenotypes with respect to a given killer toxin (Chang et al, ; Makower & Bevan, ; Pieczynska, de Visser, & Korona, ).…”
Section: Introductionmentioning
confidence: 99%
“…Killer toxin production has been related in S. cerevisiae with the presence of two dsRNA viruses: L-A, the helper virus, and the M killer virus that encodes a killer toxin that determines its phenotype (K1, K2, K28 or Klus). Although killer toxins could imply an important competitive advantage, it has also been demonstrated that there is a fitness cost for carrying mycoviruses [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Pichia acaciae , Kluyveromyces lactis and Debaryomyces robertsiae cytoplasmic virus like elements encode toxic anticodon nucleases along with specific proteins that confer toxin immunity [13,14]. The potential use of killer yeasts and their toxins has been intended for various fields of application such as the alcohol fermentation industries (brewery, winery, and distillery), fermented vegetables, biological control of post-harvest diseases, yeast bio-typing, as antimycotics in the medical field and they have been used as model systems to understand eukaryotic polypeptide processing and expression of eukaryotic viruses [10,11,12,13,14,15,16,17,18,19,20,21]. …”
Section: Introductionmentioning
confidence: 99%